Temperature threshold testing: a systematic review. Issue 1 (22nd March 2013) - Bakkers, Mayienne; Faber, Catharina G.; Peters, Martine J. H.; Reulen, Jos P. H.; Franssen, Hessel; Fischer, Tanya Z.; Merkies, Ingemar S. J.
Abstract The diagnosis of small fiber neuropathy (SFN) has been recently defined as typical symptoms due to small nerve fiber dysfunction accompanied by reduced intra‐epidermal nerve fiber density (IENFD) or abnormal temperature threshold testing (TTT). Guidelines have been published for the assessment of IENFD. However, international guidelines for TTT are lacking. This paper presents a systematic literature review on reported TTT methods and provides recommendations for its future use in studies evaluating patients. A total of 164 papers fulfilled pre‐defined requirements and were selected for review. Over 15 types of instruments are currently being used with a variety of methodological approaches for location, stimulus application, and sensation qualities examined. Consensus is needed to standardize the use of TTT as a diagnostic and follow‐up tool in patients.